Content Analysis of Da’wa Message in “Laa Tahzan: Don’t Be Sad” Episode #71 - #80 On Line Webtoon - Prihananto, Prihananto; Rachman, M. Faizal; Nisak, Fika Khoirotun (Proceedings of International Conference on Da'wa and Communication, 2020)
The focus of the problems studied in this thesis is: How is the message of da’wa contained in the Webtoon "Laa Tahzan: don't be sad" episode #71 - #80. The purpose of this is to find out the message of da’wa contained in the Webtoon "Laa Tahzan: don't be sad" episode #71 - #80. The method used in this research is the content analysis which is quantitative in nature, namely by recording the values ​​of numbers or frequencies to describe various types of defined content. The technique of collecting data is by observing and documenting further analysis according to predetermined indicators. In this study, the researcher conducted a content analysis of the da’wa messages contained in the Webtoon "Laa Tahzan: don't be sad" episode #71 - #80. After being calculated and analyzed, the results showed that the da’wa messages contained in the Webtoon were 28% in the form of creed messages, 60% in the form of moral messages, and 12% in the form of sharia messages. Then the message of the most dominant da’wa is the message of morality with a percentage of 60%.